Merumuskan Konsep Fiqh Islam Perspektif Indonesia - Mahathir Muhammad Iqbal (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2017)
Abstract fiqh is that it is not a revelation from heaven. Fiqh is the product of ijtihad. The issue of who is to formulate it, for what purpose, under what social conditions are formulated, and the geographic locus as to what, with what epistemology, quite a big influence on the process of formation of fiqh. In other words, the fiqh is not grown in the empty space, but moving in the flow of history. Each product fiqh thinking always an interaction between the thinker with the socio-cultural and socio-political surrounds. In an atmosphere and conditions such that the entire Islamic law is written. It seems logical that the classical fiqh thinking configuration and placed in the general context of the current thinking fiqh produced on the one hand, and in the context of a particular epistemological on the other side. Knowing these contexts is not only essential in the enrichment of the social history of jurisprudence, but also very useful for the preparation efforts of the new jurisprudence, fiqh which rests on the fulcrum of the problems of humanity in a state of Indonesian society. Keywords: Fiqh, Sociocultural, sociopolitical   Abstraksi fiqh adalah bahwa ia bukan wahyu dari langit. Fiqh merupakan produk ijtihad. Persoalan siapa yang merumuskannya, untuk kepentingan apa, dalam kondisi sosial yang bagaimana dirumuskan, serta dalam lokus geografis seperti apa, dengan epistemologi apa, cukup besar pengaruhnya di dalam proses pembentukan fiqh. Dengan perkataan lain, fiqh tidak tumbuh dalam ruang kosong, tetapi bergerak dalam arus sejarah. Setiap produk pemikiran fiqh selalu merupakan interaksi antara si pemikir dengan lingkungan sosio-kultural dan sosio-politik yang melingkupinya. Dalam suasana dan kondisi seperti itulah seluruh fiqh Islam ditulis. Kiranya logis jika pemikiran fiqh klasik tersebut diletakkan dalam konfigurasi dan konteks umum pemikiran saat fiqh tersebut diproduksi di satu sisi, dan dalam konteks epistemologis tertentu di sisi lain. Mengetahui konteks-konteks tersebut bukan hanya penting dalam pengayaan sejarah sosial fiqh, melainkan juga sangat berguna bagi upaya penyusunan fiqh baru, fiqh yang berlandas tumpu pada problem-problem kemanusiaan dalam kondisi obyektif masyarakat Indonesia.   Kata Kunci: Fiqh, Sosiokultural, Sosiopolitik